LITERATUR REVIEW MULTIMODAL AFFECTIVE SPEECH AND EMOTIONAL EXPRESSION - Muhamad Fatchan; Andri Firmansyah; Wahyu Hadikristanto (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2019)
Affective computing in a new field that is closely related to human and computer interaction, the result of developing intelligent systems that are capable of recognizing human emotional data processing, the rapid development of computational technology in terms of hardware and software demands to meet the service needs of users, various computational technologies which is now easily available like smartphones and gadgets. Giving training skills to computers to be able to better interact with users to handle users' emotional communication aspects, for this reason machine sensing training cannot be separated from advanced service needs for users, this research focuses on advanced computing such as the introduction of facial expression emotions the user continues to develop the issue of recognizing facial effects in humans by extracting features from different human images.